2008
DOI: 10.18546/ijsd.06.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Each One, Teach One: A methodological approach for national disaster school response

Abstract: Background Hamline University, a medium sized college in St. Paul Minnesota, dedicated resources and time to New Orleans, Louisiana in its efforts to rebuild and reclaim the city. Days after Hurricane Katrina hit, Hamline sent students, faculty and staff to help with recovery efforts. The Education Club adopted Martin Luther King Science and Technology school (MLK) soon after to help in cleaning and rebuilding the school and sent over $20,000.00 in books, supplies, merchandise gift cards, food and water to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, taken as a whole, empowerment was less likely to be associated with one‐to‐one tuition than other forms of online and blended learning (e.g. Condie & Livingston 2007; Strait & Jones 2009).…”
Section: Dimension 2: Co‐constructionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, taken as a whole, empowerment was less likely to be associated with one‐to‐one tuition than other forms of online and blended learning (e.g. Condie & Livingston 2007; Strait & Jones 2009).…”
Section: Dimension 2: Co‐constructionmentioning
confidence: 92%
“…This has been reinforced outside the core studies by Strait and Jones (2009) and Whitney (2007), who found that most of the literature around the use of technology in literacy focused on the development of cognitive processes among students, rather than on engagement or motivation. It should also be noted that Barker (2002) and others' claim that teachers need to develop such technical skills more than students who may have honed their digital habits outside of formal education has been echoed by other research into technology-based learning (e.g.…”
Section: Developing Students' Skills and Digital Literaciesmentioning
confidence: 95%
“…Strait suggests finding ways for community partners to contact the instructor or person in charge of the project. The budget for a project is another important aspect, which takes extensive planning (Strait & Jones, 2009). The budget proposal for any project should be very detailed and specific.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To respond effectively, school counselors must have a broad range of knowledge about community resources available to aid in disaster response (Razi & DeChillo, 2005). Partnerships with community resources were found to be essential in crisis response within schools after Hurricane Katrina (Strait & Jones, 2009). Many communities have well-established entities, such as faith-based, recreational, and social organizations, that can be beneficial partners for school counselors to access needed resources for their students following a disaster (West-Olantunji & Goodman, 2011).…”
mentioning
confidence: 99%
“…Many communities have well-established entities, such as faith-based, recreational, and social organizations, that can be beneficial partners for school counselors to access needed resources for their students following a disaster (West-Olantunji & Goodman, 2011). Strait and Jones (2009) also asserted that communities have the ability to experience resilience and a sense of hope in moving forward when coming together in resourceful ways to meet each other’s needs after a disaster.…”
mentioning
confidence: 99%